Bacteriological Profile and Antibacterial Sensitivity Patterns of Isolates among Burn Patients in Sulaimani - Rashid, Kamal Jalal; Babakir-Mina, Muhammed; Abdilkarim, Dana Abdilmajid; Hama Rahim, Bestun Ibrahim; Mohammed, Sarko Masood (Kurdistan Journal of Applied Research, 2017)
Nosocomial infections have increasingly been implicated in transferring fatal septic complications in burn patients. Also multidrug resistant profiles of microorganisms are being increasingly found in burn wounds which are very much alarming due to the limited number effective antibacterial drugs. Retrospective data were collected from burn patients at Sulaimani Burn and Plastic Surgery Hospital between January 2013 and December 2015. Culture& sensitivity tests were performed using wound surface swabs and tissue culture over the three year period. Their results were collected in a predesigned digital form. Statistical analysis was done and results plotted. Out of 500 burn positive swabs samples were previously taken from hospitalized patients, the commonest bacterial isolate were gram-positive bacterial infection; Methicillin-Resistant Staphylococcus Aureus (MRSA) 215(43%) followed by gram-negative bacterial infection; Acinetobacter baumannii and Pseudomonas aeruginosa 95(19%) and 85 (17%). Vancomycin has no any resistant rate for all gram-positive bacteria followed, but Teicoplanin is the second best drug especially, for MRSA 8.4%. Imipenem and Meropenem are antibiotics with no or less resistant rates for most of gram negative bacteria. Resistance to antibiotics is rapidly increasing in our community and burn wounds are frequently infected by these multidrug resistant organisms. Careful antibiotic selection and effective control of these strains can be translated into lower morbidity and mortality for these patients.